Impact of tourism on roundabout of economic process - Vujovic, Slavoljub; Curcic, Nikola; Miletic, Vuk (Ekonomika poljoprivrede (1979), 2016)
The relation between of production and consumption units, market mechanisms, and the behaviour of economic subjects in the market are aspects that enable an understanding of tourism in the economic process. Two basic factors of tourism "free time and free money" as the goal of creation of each individual, striving to meet the needs for luxury, rest, rehabilitation and recreation, are directly linked to the basic economic relationship, the relationship between limited resources and unlimited needs. Not respecting the principles and rules of the socio-economic sphere, by the dynamics of the development of techno-economic sphere, the increasing difference between the poor majority and rich minority in the world, causing many economic and social problems. Given the economic problems on a global level, further directions of development of tourism should be sought through the analysis of the relationship, or better to say, interdependence of development of techno-economic and socio-economic spheres. This paper seeks to determine and clarify the importance of tourism as a factor stimulating circular flow of economic processes.